Authentic Assessments or Standardized Assessment New Attitude to Architecture Assessment - Badiossadat, Hassanpour; Nurakmal, Abdullah@ Goh Tuo Ho; Nangkula, Utaberta; Spalie, -; Mazlan, Mohd Tahir (Elsevier Science, Ltd., 2011)
To know about an educational system, we must look to its assessment procedures. Assessment is the process of seeking and interpreting evidence for use by learners and their teachers to decide where they are in their learning, where they need to go and how best to get there. Assessment should not be seen separable from instruction, but also as a powerful tool for promoting deep learning activities. Assessment culture refers to educational evaluation practices that are compatible with current ideologies, social expectations, attitudes and values so the emergence of assessment cultures needs to be discussed with reference to current views on learning and education. The target of this paper is to understand whether same methods in architectural pedagogy can satisfy different learning styles, different backgrounds and cultures or not.